Lost in the trenches. Semantics of the narrative of warspaces in Erich Maria Remarque’s “All Quiet on the Western Front” - Brylla, Wolfgang (Acta Universitatis Lodziensis. Folia Germanica, 2014)
During the centenary of the outbreak of the First World War Erich Maria Remarque’s bestseller “All Quiet on the Western Front” is surpassing successive records of popularity. Commonly considered as an antiwar and pacifist novel, the history of Paul Bäumer, a young soldier on the western front, is rather a novel about a war generation lost in the trenches. Remarque describes this written off generation on the stage of various war-spaces. The first-person narrator who very often switches to the collective ‘we’, is the voice of virtually the whole community of combatants engaged on the side of the German recruits, describes 1) barracks in which it has been attempted to destroy their youth and build their new identity, 2) the latrine at the front that paradoxically secures relative peace for them, 3) earthworks as a prelude to hostilities, 4) trenches/dugouts that are only a waiting-room for death, 5) the home front which is presented in the context of “La Grande Guerre” as an alien and impersonal space, and 6) the military hospital that from the narrator’s Bäumer’s perspective is the war in a minature format. The homodiegetic and autodiegetic method of narration in “All Quiet on the Western Front” is on the one hand based on the visualization of the war-spaces, on the other – on showing, through the making of the narrative semantics of these spaces, the lost generation. Bäumer’s and his companions’s moral-ethical-human fall is related to, and dependent on, the spaces in which they exist and which affect their psychic and physical condition. With the death of the main narrator also dies the space of the narration, however the frame of the narrative spaces remains and documents the cruelty and savagery of the hell of 1914–1918.